2000
DOI: 10.2307/177174
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Traits Affecting the Distribution and Wintering Strategy of the Bat Tadarida teniotis

Abstract: The ability to enter torpor at low ambient temperature, which enables insectivorous bats to survive seasonal food shortage, is often seen as a prerequisite for colonizing cold environments. Free-tailed bats (Molossidae) show a distribution with a maximum latitudinal extension that appears to be intermediate between truly tropical and temperate-zone bat families. We therefore tested the hypothesis that Tadarida teniotis, the molossid species reaching the highest latitude worldwide (46Њ N), lacks the extreme phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 19 publications
1
42
0
2
Order By: Relevance
“…They had probably entered torpor, since Arlettaz et al (2000) demonstrated that the ideal range of ambient temperatures for torpor in this species is 7.5-10ºC, unusually high for crevice roosting temperate bats. Although most of the night active period was used for foraging, a considerable amount of time was spent flying in the immediate vicinity of the roost.…”
Section: Patterns Of Activitymentioning
confidence: 95%
See 1 more Smart Citation
“…They had probably entered torpor, since Arlettaz et al (2000) demonstrated that the ideal range of ambient temperatures for torpor in this species is 7.5-10ºC, unusually high for crevice roosting temperate bats. Although most of the night active period was used for foraging, a considerable amount of time was spent flying in the immediate vicinity of the roost.…”
Section: Patterns Of Activitymentioning
confidence: 95%
“…family living in a temperate zone (Arlettaz et al, 2000). Although this peculiarity may strongly influence various aspects of the ecology and behaviour of the species, it remains one of the least known bats of the European fauna.…”
Section: Introductionmentioning
confidence: 99%
“…Among molossids, the species of the genus Tadarida seems to be the most latitudinally extended, both northward and southward. For instance, Tadarida teniotis (Rafinesque, 1814) has been recorded as far up as 46 ° N latitude (Arlettaz et al 2000 ), representing the northernmost known record for a bat. On the other hand, vespertilionids can reach even higher latitudes, considering that Myotis chiloensis (Waterhouse, 1840) was recorded at 55 ° S in Chile, which is the southernmost known record for any bat in the world (Koopman 1967 ).…”
mentioning
confidence: 99%
“…Hibernation is widespread in temperate-zone bat species that experience low environmental temperatures and reduced food availability during winter (Lyman et al 1982;Arlettaz et al 2000;Humphries et al 2002). Bats often hibernate in thermally stable microsites such as caves and buildings during winter, which allows them to maintain more-or-less constant T b between interbout normothermic periods (Lyman et al 1982;Arlettaz et al 2000;Humphries et al 2002;Boyles and Willis 2009).…”
mentioning
confidence: 99%
“…Bats often hibernate in thermally stable microsites such as caves and buildings during winter, which allows them to maintain more-or-less constant T b between interbout normothermic periods (Lyman et al 1982;Arlettaz et al 2000;Humphries et al 2002;Boyles and Willis 2009). In contrast, daily torpor appears to be a more common response in species inhabiting lower latitudes (Geiser and Brigham 2000;Turbill et al 2003;Willis et al 2005;Jacobs et al 2007;Vivier and van der Merwe 2007).…”
mentioning
confidence: 99%